An empirical study of early childhood support through partnership building. (December 2016) - Wang, Jianjun; Ortiz, Theresa; Navarro, Diana; Maier, Roland; Wang, Summer; Wang, Lisa; Wang, Libing
Highlights: This study provides an empirical report on partnership building across 40 programs funded by Proposition 10, an unprecedented child-support initiative in California. Multilevel data were analyzed across focus areas of Child Health, Family Functioning, and Child Development to confirm merit of partnership building under a CIPP model. A 4C paradigm (Co-Existing, Collaboration, Coordination, Creation) was created from a SOLO [Structure of the Observed Learning Outcome] taxonomy for partnership analyses. Abstract: The first five years were recognized as a critical period of child growth. Accordingly, California voters approved tobacco tax throughProposition 10 to fund early childhood services since 1998. Due to the state revenue decline, Service Integration has been advocated to enhance program supports in Child Health, Family Functioning, and Child Development . In this study, interview data are analyzed to examine the partnership building among 40 programs. The results indicate a significant impact of the service outreach across remote communities in Kern County, California. In addition, contextual information is provided to facilitate interpretation of the partnership strength from a social network analysis. Enhancement of this investigation is discussed in light of future development.